The Moderating Role of the Organizational Climate on the Relationship between IT alignment and Employee Performance - Asiimwe, Khadijah Namara; Bada, Joseph Kizito; Kasekende, Francis (East African Journal of Business and Economics, 2023)
Purpose: The purpose of this study was to empirically establish the moderating role of the organisational climate on the relationship between IT alignment and employee performance at Umeme Limited. Design/methodology/approach: The research used a cross-sectional approach. To test their theories, the authors use hierarchical regression modeling. A sample of 165 respondents with a 100% response rate was selected from among the 290 employees of Umeme Limited using proportionate simple random and sampling procedures. Findings: Multiple regression results indicate that Information technology alignment is a significant predictor of Employee Performance in UMEME ltd (Beta = .534, p < 0.001). This implies that Information technology alignment explains 53.4% of the variance in Employee performance. When testing for moderating role of the organisational climate on the relationship between IT alignment and employee performance at Umeme Limited, the interaction term was positive and significant, resulting in the hypothesis “organisational climate moderates the association between IT alignment and employee performance at Umeme Limited” being accepted. Practical implications: The organisational climate in which Umeme employees operate is dynamic and rapidly changing, requiring constant modification of strategies and operations to reflect these changing circumstances if employee performance is to be increased. Originality/value: This is one of the few studies that focus on testing the moderating effects of organisational climate on the relationship between IT alignment and employee performance in the Service Sector in Uganda